The effect of exercises similar to performance movements in mastering the technical stages of the skill of jumping the front hands on the floor mat - HassoonMashkoor, Shaymaa; Ammar Lifta, Iqbal (International Journal of Psychosocial Rehabilitation, 2020)
Gymnastics activities are among the sports that have gained a distinguished position in all countries of the world as a good model for individual games whose players are characterized by many different abilities and permanent preparations to act in solving performance situations during sports competition. Suggested in the skill of jumping the front hands on the carpet of ground movements and exercises similar to playing are “those exercises in which two small groups compete in order to obtain the ball and keep it or achieve a specific goal, whether with or without the two goals, similar to what happens in the match and through which the required movements can be drawn of players in different situationsIn light of the findings of the researchers, the following was concluded:The suitability of the exercises used for the research sample contributed to their correct and appropriate application.The exercises prepared have a positive effect in developing the rate of speed and frequency for the effectiveness of jumping on the horse.In light of the conclusions reached by the researchers, the following was recommended:1. The necessity of using skill exercises to develop the skill performance of other activities.2. The need to pay attention to the movements of the left and the back rotation followed by the musk, as the development in these movements at the global level largely reflects the degree of progress in the parallel device.